A Longitudinal Study of Subjective Daytime Sleepiness Changes in Elementary School Children Following a Temporary School Closure Due to COVID-19 - Yoko Komada; Yoshiki Ishibashi; Shunta Hagiwara; Mariko Kobori; Akiyoshi Shimura (MDPI AG, 2021)
Excessive daytime sleepiness is increasingly being recognized as a major global health concern. However, there have been few studies related to sleepiness and its associated factors in elementary school children. In Japan, all schools were closed from February to May 2020 to prevent coronavirus disease 2019 (COVID-19) outbreaks. The aim of this study was to identify changes in the subjective sleepiness of pupils during the 1.5-year period and to elucidate factors associated with changes in sleepiness. Questionnaire surveys about pupils' sleep habits and the Japanese version of the Pediatric Daytime Sleepiness Scale (PDSS-J) were conducted longitudinally at one elementary school in June 2019, January 2020, and June 2020. The average ∆PDSS score was 0.94 ± 5.51 (mean ± standard deviation) from June 2019 to January 2020 and −1.65 ± 5.71 (t[498] = 6.13, p < 0.01) from January 2020 to June 2020. Univariate and multivariate logistic regression analyses revealed that decreasing social jetlag was associated with decreasing PDSS scores (OR = 0.77, 95% CI: 0.62-0.96, p = 0.02) during the school closure. A less restrictive school schedule secondary to a COVID-19-related school closure decreased sleepiness in children and was associated with decreasing social jetlag.